Rapid in vitro Propagation of Boerhaavia diffusa (L.) through Nodal Segments - Saini, Gulshan Saini; Amla Batra, Rajendra Saini*, Anirudha Rishi, Shikha (Journal of Experimental Sciences, 2010)
Â <div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-border-top-alt: solid windowtext .5pt; mso-element: para-border-div;"> A rapid and efficient protocol for the large scale propagation of a potential medicinal plant Boerhaavia diffusa L., through in vitro culture of nodal segment explants obtained from aseptic seedlings. In vitro multiple shoot (14-15) induction was observed from axillary bud explants cultured on MS medium fortified with BAP (2.0 mg/l) and Kn (3.5 mg/l). The multiple shoots were separated and subcultured for their elongation on same medium supplemented with gibberelic acid (0.5 mg/l). Rooting on in vitro produced elongated shoots was achieved on half MS medium having IBA (0.5 mg/l). Rooted plantlets were hardened in plastic pots containing sterilized soil and vermiculite (3:1). Well established plantlets were acclimatized to the field with 70% survival rate. Â Key words: Medicinal plants, Nodal segments, Micropropagation, in vitro rooting Â Plant biotechnology laboratory, Department of Botany, University of Rajasthan, Jaipur 302004, Rajasthan